The Natural Polypeptides as Significant Elastase Inhibitors - Ahmad, Shabir; Saleem, Muhammad; Riaz, Naheed; Lee, Yong Sup; Diri, Reem; Noor, Ahmad; Almasri, Diena; Bagalagel, Alaa; Elsebai, Mahmoud Fahmi (Frontiers in Pharmacology, 2020)
Human neutrophil elastase (HNE) is a major cause of the destruction of tissue in the cases of chronic and different inflammatory diseases. Overexpression of the elastase enzyme is playing significant roles in the pathogenesis of various diseases including chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome, rheumatoid arthritis, the rare disease cyclic hematopoeiesis (or cyclic neutropenia), infections, sepsis, cystic fibrosis, myocardial ischemia/reperfusion injury and asthma, inflammation and atherosclerosis. Human neutrophil elastase is secreted by human neutrophils due to different stimuli. Medicine based inhibition of the over-activation of neutrophils or production and activity of elastase have been suggested to mend inflammatory diseases. Although the development of new elastase inhibitors is an important strategy for treating the different inflammatory diseases, it has been a challenge to target specifically the activity of elastase because of its overlapping functions with those of other serine proteases. This review article highlights the reported natural polypeptides as potential inhibitors of elastase enzyme. The mechanism of action, structural features, and activity of the polypeptides have also been correlated wherever they were available.